Small Photoblinking Semiconductor Polymer Dots for Fluorescence Nanoscopy - Chen, Xuanze; Li, Rongqin; Liu, Zhihe; Sun, Kai; Sun, Zezhou; Chen, Danni; Xu, Gaixia; Xi, Peng; Wu, Changfeng; Sun, Yujie (Advanced materials (Weinheim), 2017)
Two types of small photoblinking Pdots with high brightness, strong photostability, and favorable biocompatibility, are designed. Super‐resolution optical fluctuation imaging is achieved using these Pdots. Imaging of subcellular structures demonstrates that these small photoblinking Pdots are outstanding probes for fast, long‐term super‐resolution fluorescence imaging.